Research on M-Paul Dynamic Constitutive Relation of Q235B Steel - Li Lin; Bo Huang; Xinke Xiao; Minyuan Huang; Zhiying Liu (Advances in Civil Engineering)
In recent years, terrorist attacks and regional conflicts have increased and research on the resistance of building structures has been more highlighted. Q235B is a commonly used steel type in building structures, and there is an urgent need for research on its dynamic material properties. In this paper, Paul constitutive model was calibrated based on the material properties of Q235B steel. Based on the obtained results, it was found that the original model was not able to take into account temperature-softening effect. Therefore, a temperature-softening parameter was added into the temperature term of the original Paul model, and the modified M-Paul constitutive model was developed. Then, numerical prediction results obtained from Q235B steel penetration experiments using J-C (Johnson–Cook) and M-Paul constitutive models were compared. It was observed that J-C constitutive model significantly overestimated ballistic limit while estimations obtained from M-Paul constitutive model were closer to experimental results. This observation verified the correctness and effectiveness of M-Paul model and established a solid foundation for relevant research works on the impact resistance of building structures.